Phantom Breast Syndrome Post Mastectomy in Wasit Specialized Oncology Center - Mohsin, Talib Saddam; Dilfy, Saja Hussain (American Journal of Biology and Natural Sciences, 2025)
Phantom breast syndrome (PBS) is a type of condition in which patients have a sensation of residual breast tissue and can include both non-painful sensations as well as phantom breast pain. Present study aimed to determine phantom breast syndrome post mastectomy in Wasit Specialized Oncology Center. The current study included collecting a questionnaire from 100 women suffering from breast cancer and the phantom condition. The results of our study showed that 27% of patients suffered from phantom breast cancer pain, while the majority (73%) had a feeling of the presence of breast tissue but without pain. We found that phantom breast cancer pain appeared in a rate of 96% in the case of unilateral and 4% in the case of bilateral breast cancer, while the rates were 89% and 11% for both unilateral and bilateral breast cancer in patients not concerned with phantom breast pain (P value > 0.05). Modified radical mastectomy appeared in 88% and 85% of non painful and painful phantom breast cancer respectively whereas simple mastectomy determined in 12% and 15% of them respectively. We found statistical differences (X2 = 3.95, P value = 0.036) when evaluating phantom pain for breast cancer according to the age groups of patients. The study showed that the onset of feeling breast pain ranged from 1 to 9 months after breast lift surgery, with an average of 3.22 months and continued for a duration of 2 to 4 months, with an average of 2.14 months. Most (44%) of the patients had a phantom pain onset less than 3 months after the mastectomy. Conclusion: Phantom breast pain appeared in 27% of patients three months after the operation and continued for approximately two months. Phantom breast pain mainly associated with unilateral modified radical mastectomy and significantly different with age.